Peningkatan Kesejahteraan Ekonomi Masyarakat Pesisir Melalui Pemberdayaan Perempuan - Donna NP Butarbutar; Lelo Sintani; Luluk Tri Harinie (Journal of Environment and Management, 2020)
This study examines the strategy of community economic welfare improvement through empowering coastal women in utilizing fishery waste products. The informants were purposively pick up from those who attended the training of waste processing of fishery products and took the follow-up training. Additional data were collected through observation, interview and documental study. The cumulative data were then examined used SWOT analysis. The results show that the workable strategy was SO (Strengths–Opportunities) strategy, namely using internal strengths to get the advantage from external opportunities. The weaknesses needs for improvement were lack of skill, lack of tools or equipment to process the products, lack of funds, unregistered business body and limited market. Meanwhile, the threats from competitors of similar products, unavailability of product distributors, consumer demand for more creative products, and rapid technological development are hard to follow by coastal women.